2022
DOI: 10.1371/journal.pgph.0000188
|View full text |Cite
|
Sign up to set email alerts
|

Influence of climate variables on dengue fever occurrence in the southern region of Thailand

Abstract: The 3-5year epidemic cycle of dengue fever in Thailand makes it a major re-emerging public health problem resulting in being a burden in endemic areas. Although the Thai Ministry of Public Health adopted the WHO dengue control strategy, all dengue virus serotypes continue to circulate. Health officers and village health volunteers implement some intervention options but there is a need to ascertain most appropriate (or a combination of) interventions regarding the environment and contextual factors that may un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…It is important to understand how the interactions between climatic factors over past decades have defined infection trends and risks, unique to every region. Results of previous studies have shown that mean annual temperature, sea level pressure, number of days of rainfall and wind speed are among the variables having a significant influence on the rate of occurrence of dengue fever in the study area ( Abdulsalam et al, 2022 ), which was confirmed in this study ( Table 1 ). In coastal areas, temperature and precipitation tend to be higher and the study region is located in a coastal region (the Gulf of Thailand).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…It is important to understand how the interactions between climatic factors over past decades have defined infection trends and risks, unique to every region. Results of previous studies have shown that mean annual temperature, sea level pressure, number of days of rainfall and wind speed are among the variables having a significant influence on the rate of occurrence of dengue fever in the study area ( Abdulsalam et al, 2022 ), which was confirmed in this study ( Table 1 ). In coastal areas, temperature and precipitation tend to be higher and the study region is located in a coastal region (the Gulf of Thailand).…”
Section: Discussionsupporting
confidence: 86%
“…In coastal areas, temperature and precipitation tend to be higher and the study region is located in a coastal region (the Gulf of Thailand). While there may not be a substantial change in geographical patterns over time, there is a visible increase in precipitation in the region for the past decade ( Abdulsalam et al, 2022 ) and from April to October, increasing temperature and precipitation levels also increase mosquito density ultimately driving up the number of reported dengue cases. The temporal trend in dengue incidence risk observed in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indonesia is an archipelagic country, until 2021 there were 1,331 tribes and 488 Customary Villages [19], this makes the variables that affect the breeding and reproduction of dengue vectors very large and complex [20] because each tribe and custom have different characteristics. Risk factors for potential vector breeding places and physical environment can provide important information to fill the gap in our knowledge about dengue vector dynamics, especially data related to indigenous peoples in Indonesia, which so far has not been available.…”
Section: Introductionmentioning
confidence: 99%